EDUKASI PENGGUNAAN TEKNOLOGI DIGITAL SECARA BIJAK UNTUK MENCEGAH DAMPAK NEGATIF PADA SISWA/I MADRASAH TSANAWIYAH NURUL HUDA KOTA JAMBI - Munandar, Aris; Rahmadani, Agil; Aini, Syafira; Renaldi, Rahman; Rizky, Fathul; Zakia; Yusuf, Ja'far Maulana; Cahyani, Annisa Dwi; Febriana, Novita Susanti; Endriyani, Leni (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2025)
This community service program aims to educate students of Madrasah Tsanawiyah Nurul Huda Kota Jambi about the wise and responsible use of digital technology to minimize negative impacts such as cyberbullying, hoaxes, and online addiction. The method used invloved socialization, workshops, and mentoring sessions involving 28 students from grades 7 to 9. Evaluation was conducted using pre-test and post-test questionnaires and group discussions. The results showed an increase in students’ digital literacy and awareness of online ethics by 30–40%. Students demonstrated better understanding of how to verify information and maintain positive online behavior. The program is expected to encourage sustainable digital literacy education in schools and foster ethical digital citizenship among adolescents.